Community Culture: Sustainability, Conservation for Integration of theTeaching of Civil Duty and Morals Thai Arts and Culture Unit, Phrae Technical College - Singkham, Jirapinya; Kumhom, Naitawan (RATANABUTH JOURNAL, 2022)
Community Culture Research: Collect information that will help you determine the curriculum of the community group function. And the following example is a Thai example. Don't forget to leave Muang Phrae District. Phrae Technical College The population and the specific sample consisted of 1) knowledge groups, i.e. people with in-depth information about cultural tourism. 2) The group of practitioners is teachers, students, villagers who have traveled. 3) The general group is the general public who have known or used to travel. This research used a qualitative cultural research method. The tools for data collection were surveys, interviews, observational forms, small group meetings and workshops. The results of the research were as follows; 1) Tourist routes can travel locally in 3 main routes. The researcher chooses the first route which is Wat Si Chum->Wat Phrabat Ming Mueang Worawihan->Khum Chao Luang Mueang Phrae->Mueang Phrae Pillar Shrine->Khum Wichai Racha, ancient city legend of Phrae->Mueang Phrae Forestry Museum->Wat Phra Non->Ban Wongburi ->Wat Luang->Wat Hua Khuang ->Wat Chom Sawan->Seri Thai Museum->Wat Sa Bo Kaeo->Wat Si Chum, which has unique traditions and customs. There is an environment in the area to be outstanding. According to the landscape geography and history of that area activities are supported travel culturally such as, Kad Kong Khao Phrae, Phrae Walking Street. There are tourism resources of each community example, silver handicrafts. goldware and tamarind product of Ban Phra Non community, Morhom cloth of Ban Thung Hong community. It is organized in the form of demonstrations and experiments with local cooking. such as Khanom Jeen Nam Moo Phrae, Laab Mueang Phrae. 2) Integration of Civil Duty and Morals Teaching Thai Arts and Culture Unit Phrae Technical College, it has integrated in the course code 20000-1501, Civil Duty and Morals Thai Art and Culture unit on Thai culture, about Thai wisdom by using the first path, which has the following steps which has the following steps 1) Set up a committee at the school level. 2) Analyzing the learning framework, Thai wisdom, set by educational institutions. 3) Analyze the curriculum of the educational institution in order to know the focus or issues that educational institutions focus on. 4) Study/analyze information of educational institutions and communities to be used as information about Thai wisdom. 5) Prepare the learning material Thai wisdom of educational institution and to manage teaching by using worksheets, and the study of the actual place.